CRIMINAL LIABILITY FOR COLLABORATIVE ACTIVITIES IN THE CONTEXT OF CRIMINAL LAW PROVISION RELATED TO STATE SECURITY - Komissarov, Mykola; Komissarova, Natalia (Honor and Law, 2023)
The article examines the issues of implementation of the Law of Ukraine "On Amendments to Certain Legislative Acts of Ukraine on Criminalization of Collaboration Activities" No. 2108-IX dated 03.03.2022 in the context of ensuring the State security of Ukraine. The author analyses the elements of the crime under Article 1111. The author provides the features which distinguish this crime from other criminal offences. The author suggests approaches to improving the legal acts in the field of state security and criminal law through the use of successful legal and commonly used terms. The author considers the criteria which could serve as a basis for the creation and improvement of legislation in general and criminal law in particular. It is emphasized that since 2014, the issue of bringing to justice before the State and the people of Ukraine therefore citizens of Ukraine who actively cooperate with the aggressor country and whose actions are not covered by the crime under Article 111 of the Criminal Code of Ukraine "High Treason" has become very relevant in Ukraine. It is noted that, according to this Law of Ukraine "On National Security of Ukraine", state security is defined as the protection of state sovereignty, territorial integrity and democratic constitutional order and other vital national interests from real and potential non-military threats. It is emphasized that the key terms of the definition of state security are "security" and "non-military threats". It is argued that these categories indicate the priority of the legal plane of state security protection through legislative regulation of social processes which are potentially and actually dangerous for state and national security.